Education on the Go: Studying the Use of Podcasts in Resident Education. (October 2017) - De Los Reyes, Samaqntha; Cholakian, Diana; Chau, Danielle; Forde, Braxton; Johnson, Clark; Bienstock, Jessica
Abstract : BACKGROUND: Podcasting has become a mainstream media commodity, although its implementation into medical education has yet to be studied. Podcasting curricula can be readily created and disseminated for educational efficiency. METHODS: Four podcasts were created to cover information from American College of Obstetricians and Gynecologists' Practice Bulletins. All residents in our academic program were randomized to access the bulletins or both podcasts and bulletins. Both groups were offered posteducation quizzes. Outcomes included resident quiz completion as well as overall performance. Analysis was performed using standard statistics in Stata 14, with significance defined as P <.05. This project was IRB-approved. RESULTS: Overall, 126 quizzes were administered to 36 residents. Thirty-eight (30.2%) posteducation quizzes were completed, including 16 (27.6%) from residents who received podcasts and 22 (32.4%) from those who did not, a difference that was not statistically significant ( P =.56). Similarly there was no significant difference in average quiz scores between podcast and traditional groups (70±22.3% and 80±17.1% respectively, P =.17). DISCUSSION: Podcasts have become an efficient and popular way for residents to learn. We noted equivalent participation and comprehension of the curriculum whether or not podcasts were used in conjunction with self-directed reading. The addition of podcasts to a resident curriculum may not significantly improve scores or participation. Future studies may evaluate the efficiency of education through podcasting in the ob/gyn residency given its noninferiority to traditional self-directed learning.